2021
DOI: 10.1088/1361-648x/ac1180
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio investigation on the electronic and thermoelectric properties of new half-Heusler compounds KBiX (X = Ba and Sr)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Figure 6 represents the Seebeck coefficient ( S ), electrical conductivity ( ), and electronic thermal conductivity ( ) for both PdZrSn and PdHfSn materials at various temperatures (300 K, 500 K, 700 K). According to Mott’s formula [ 27 ], the Seebeck coefficient is directly proportional to DOS effective mass and temperature but inversely proportional to carrier concentration. It is given by …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 represents the Seebeck coefficient ( S ), electrical conductivity ( ), and electronic thermal conductivity ( ) for both PdZrSn and PdHfSn materials at various temperatures (300 K, 500 K, 700 K). According to Mott’s formula [ 27 ], the Seebeck coefficient is directly proportional to DOS effective mass and temperature but inversely proportional to carrier concentration. It is given by …”
Section: Resultsmentioning
confidence: 99%
“…Thermoelectric properties of KBiX (X = Ba, Sr) were investigated by Z.F. Meghoufel et al using ab initio principle, and they found the values of ZT = 2.68 and 1.56 for KBiBa and KBiSr, respectively [ 27 ]. R. Ahemad et al reported ZT = 1 for all XMgN (X = Li, La, K) half Heusler materials [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“… 29 For KBiX (X = Ba, Sr), based on theoretical calculation, ZT reached 2.68 (1.56) for KBiBa (KBiSr). 30 J. Carrete used an ab initio method to screen a batch of structurally stable HH compounds and predicted that the materials had small lattice thermal conductivity. 31 J. H. Liu applied a compressed-sensing approach to evaluate the lattice thermal conductivity with significantly high accuracy, 32 where RhBiX (X = Ti, Zr, Hf) was within the range of their predicted HH compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the different moduli (B and V) are determined from the Voigt-Reuss-Hill approximations (VRH) [34,35], where B, G, Y, longitudinal (𝒗 𝒍 ) and transverse(𝒗 𝒕 ) velocities are written as [36] B =…”
Section: Elastic Constantsmentioning
confidence: 99%
“…Elastic constants in Table 1 computed for the SrBaSn alloy in its type-2-type groundstate stable structure include (C 11 , C 12, and C 44 ), shear (G)/bulk (B)/Young (Y)) moduli, Poisson's (ν), Pugh ratio (B/G), etc. Stability criterion proposed by Born-Huang [33] presumes the mechanical stability of SrBaSn in its Heusler structure form and is written in the form Later, the different moduli (B and V) are determined from the Voigt-Reuss-Hill approximations (VRH) [34,35], where B, G, Y, longitudinal (v l ) and transverse (v t ) velocities are written as [36]…”
Section: Elastic Constantsmentioning
confidence: 99%